Frege’s puzzle and the a priori - Cantero-Flores, Víctor (2015)
In this paper I offer a reconstruction of Stavroula Glezakos’ claim that there is no Frege’s puzzle. I identify the main theses doing the philosophical work in her argument and examine a possible difficulty: her argument may have the consequence of ruling out all a priori knowledge. I try to dispel the difficulty and restore her argument.